N-Glycosylation Is Important for Halobacterium salinarum Archaellin Expression, Archaellum Assembly and Cell Motility - Zaretsky, Marianna; Darnell, Cynthia L.; Schmid, Amy K.; Eichler, Jerry (Frontiers in Microbiology, 2019)
Halobacterium salinarum are halophilic archaea that display directional swimming in response to various environmental signals, including light, chemicals and oxygen. In Hbt. salinarum, the building blocks (archaellins) of the archaeal swimming apparatus (the archaellum) are N-glycosylated. However, the physiological importance of archaellin N-glycosylation remains unclear. Here, a tetrasaccharide comprising a hexose and three hexuronic acids decorating the five archaellins was characterized by mass spectrometry. Such analysis failed to detect sulfation of the hexuronic acids, in contrast to earlier reports. To better understand the physiological significance of Hbt. salinarum archaellin N-glycosylation, a strain deleted of aglB, encoding the archaeal oligosaccharyltransferase, was generated. In this ∆aglB strain, archaella were not detected and only low levels of archaellins were released into the medium, in contrast to what occurs with the parent strain. Mass spectrometry analysis of the archaellins in aglB cultures did not detect N-glycosylation. aglB cells also showed a slight growth defect and were impaired for motility. Quantitative real-time PCR analysis revealed dramatically reduced transcript levels of archaellin-encoding genes in the mutant strain, suggesting that N-glycosylation is important for archaellin transcription, with downstream effects on archaellum assembly and function. Control of AglB-dependent post-translational modification of archaellins could thus reflect a previously unrecognized route for regulating Hbt. salinarum motility.